Bio-inspired functionalization of very fine aggregates for better performance of cementitious materials. (30th April 2020) - Fang, Yi; Wang, Jialai; Qian, Xin; Wang, Liang; Lin, Guangping; Liu, Zhongqi
Highlights: A functionalization method is proposed to increase use of very fine sand in concrete. Dopamine can bind to diverse surfaces through covalent and non-covalent interactions. Dopamine coating can activate the inert sand to achieve better adhesion with cement paste. Significant improvement on the performances of cement mortar is achieved by the method. Abstract: Alternative sands such as manufactured sands and dune sands are commonly used due to the shortage and depletion of reserve and supply of natural aggregates in many areas. These alternative sands usually have much more very fine particles (VFPs) than the natural sands. To promote applications of these VFPs in concrete, this study employs dopamine to functionalize the surface of these VFPs to achieve better adhesion between the VFPs and the cement paste. This study is biologically inspired by mussels, which display an extraordinary ability to adhere to underwater substrates using adhesive proteins L-3, 4-dihydroxyphenylalanine (DOPA) in the mussel byssus. Dopamine, as a mimic of the DOPA, has similar strong binding ability to diverse surfaces through covalent and non-covalent interactions, which can modify the surface of VFPs and activate the inert very fine sand. To this end, the VFPs were immersed in an aqueous solution of dopamine at different durations (1 h, 6 h and 24 h) and concentrations (1 g/L, 2 g/L, and 3 g/L) with 10 mM tris buffer (pH 8.5) to produce a polydopamine coating on the surface of the VFPs. A significant improvement of the compressive strength of the concrete has been achieved by using the functionalized VFPs.